E-servqual Analysis on Tokopedia Application (Case Study on Generation Z in DKI Jakarta) - Niman, Crystal (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
E-Servqual or Electronic Service Quality is an important part of an e-commerce that relates to how users assess existing services. This study aims to determine E-Servqual on the Tokopedia Application according to Generation Z in DKI Jakarta. This study uses five dimensions, namely Tangibility, Reliability, Responsiveness, Assurance, and Empathy. Data collection was carried out using a questionnaire method distributed online. The population in this study are users of the Tokopedia application who are included in the Generation Z category in DKI Jakarta. A sample of 130 respondents was obtained according to the research criteria. Instrument tests were carried out using SPSS version 27 software for validity and reliability tests. Data is processed using Descriptive Analysis techniques, Zone of Tolerance, and E-Servqual. The results of this study are that the Tokopedia Application E-Servqual has not met the expectations of Generation Z in DKI Jakarta. Based on the Zone of Tolerance analysis, it is found that E-Servqual on all attributes can no longer be tolerated by users. Based on the E-Servqual Gap analysis, all attributes have a minus gap with the Empathy, Responsiveness, and Assurance dimensions occupying the highest average gap in order and needing immediate improvement.